1981
DOI: 10.1113/jphysiol.1981.sp013910
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of myocardial capillary permeability by albumin in the isolated, perfused rabbit heart.

Abstract: SUMMARY1. Capillary permeability-surface area products for 22Na, 56Cr-EDTA (mol. wt. 357), [57Co]cyanocobalamin (mol. wt. 1353) and 1251-labelled insulin (mol. wt.-6000) were measured using the single-passage, multiple-tracer dilution technique in isolated rabbit hearts perfused at constant flows between 0-2 and 4-7 ml. min-. g9.2. In hearts perfused with a Krebs-Ringer solution containing bovine albumin (10 g . 1.-i), the permeability-surface area products for 51Cr-EDTA and [57Co]cyanocobalamin increased as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 30 publications
(33 reference statements)
4
29
2
Order By: Relevance
“…Using Crone's method for estimating the product of capillary permeability and surface area (PS), Alvarez and Yudilevich (3) observed that the ratios of solute permeability to free diffusion coefficient (P/D) were very nearly the same for urea, glycerol, glucose, sucrose, and inulin. This fact was confirmed by other researchers using the same technique (10,45), and refinements of the methods for tracer analysis have not changed the observation (9). This result implies that permeation of these solutes is dependent only on the solute diffusion coefficient and not on any steric hin-drance due to glycocalyx or cell walls; the cleft widths between adjacent endothelial cells must be at least 10-20 nm for this to be true.…”
supporting
confidence: 73%
“…Using Crone's method for estimating the product of capillary permeability and surface area (PS), Alvarez and Yudilevich (3) observed that the ratios of solute permeability to free diffusion coefficient (P/D) were very nearly the same for urea, glycerol, glucose, sucrose, and inulin. This fact was confirmed by other researchers using the same technique (10,45), and refinements of the methods for tracer analysis have not changed the observation (9). This result implies that permeation of these solutes is dependent only on the solute diffusion coefficient and not on any steric hin-drance due to glycocalyx or cell walls; the cleft widths between adjacent endothelial cells must be at least 10-20 nm for this to be true.…”
supporting
confidence: 73%
“…Adult New Zealand rabbits of either sex and 2-4 kg in weight were sacrificed by a rapid blow to the head. The hearts were excised and immediately perfused through a cannula in the aorta at a constant flow rate of approximately I ml min-' g-' (Mann, 1981). The coronary sinus effluent drained from the ventral surface of the horizontally mounted heart.…”
Section: Methodsmentioning
confidence: 99%
“…In these experiments hearts were perfused at flow rates between 0-9 and 2-2 ml min-g'l. Following a bolus injection (100 #1 in 1-2 s) of an isotope mixture containing 1251-labelled albumin (intravascular reference tracer), D-[3H]mannitol (extracellular tracer) and L-[8-'4C]noradrenaline into the perfusate tubing close to the aorta, the coronary sinus effluent was immediately collected at regular intervals (Mann, 1981). These venous samples were directly counted in a Packard y spectrometer set for the spectrum of 121I.…”
Section: Noradrenaline Influx Kinetics In the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…1) or 18 weeks (data not shown). The continuous increase in flow was probably due to washout of albumin, as discussed previously (19) . Transcapillary insulin transfer in hearts from animals aged 7 and 18 weeks.…”
Section: Resultsmentioning
confidence: 67%